Physicochemical Characteristics of Anopheles Mosquito Breeding Sites in Azare, Bauchi State, Nigeria: Implications for Malaria Transmission and Control (Journal of Environmental Microbiology and Toxicology, 2025)
The physicochemical parameters of breeding sites of African malaria vector mosquitoes were investigated in Azare town, Bauchi State, Nigeria. A multiparameter pH meter was used to analyze water samples from various breeding sites for parameters such as temperature, pH, turbidity, dissolved oxygen, total dissolved solids, and conductivity. The results showed that the mean temperature (30.9°C and 31.1°C), pH (6.8 and 7.3), and dissolved oxygen (4.32 mg/L and 3.99 mg/L) were within the tolerable limits for mosquito breeding in Sudan and Sahel savannah regions, respectively. However, the levels of turbidity, total suspended solids, chloride, nitrate, nitrogen, and potassium exceeded the recommended limits in both regions, indicating potential anthropogenic influences. The study highlights the importance of understanding these parameters in developing targeted control strategies to reduce malaria transmission in Azare town and similar environments.
Keywords: Anopheles; Malaria; Physicochemical; Breeding sites; Nigeria